Fiscal stress as a catalyst for public service provision in China: evidence from the VAT reform - Cai, Xiaoshan; Zhang, Bin; Yang, Jin (Frontiers in Sociology, 2025)
Local government responses to fiscal stress are crucial for ensuring public service provision, especially in times of fiscal tightening. Previous studies have shown inconsistent findings, often focusing on developed countries in Europe and the United States. This study uses China's 2016 VAT reform as a quasi-natural experiment and applies a generalized difference-in-differences (DID) model to investigate the impact of fiscal stress on local government public service provision. The results reveal that fiscal stress promotes, rather than constrains, public service provision. The findings remain robust after a series of sensitivity tests. Furthermore, fiscal stress is found to be more conducive to enhancing public service provision in regions with lower fiscal decentralization, high-intensity intergovernmental competition, and higher fiscal transparency. This paper highlights the importance of a country's unique fiscal decentralization system and government performance evaluation goals in shaping local government behavior under fiscal stress. The findings provide valuable insights for improving fiscal allocation efficiency and guiding local government responses, with broader implications for similar studies in other developing countries.